2018
DOI: 10.1016/j.gore.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Using advanced wound care and hyperbaric oxygen to manage wound complications following treatment of vulvovaginal carcinoma

Abstract: Postoperative management of patients with vulvar cancer is associated with a high incidence of poor wound healing and radiation -induced late tissue necrosis. This case series demonstrates the impact on wound healing with the use of hyperbaric oxygen therapy and advanced wound care following radical vulvectomy and/or radiation therapy.A retrospective case series was performed of all patients from 2016 to 2017 with lower genital cancer who underwent radical surgery with or without chemoradiation treatment, expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In hyperbaric oxygen treatment (HBOT), patients are treated with 100% oxygen under pressures higher than 1.4 absolute atmospheres (ATA), usually to promote wound healing, dilute carbon monoxide poisoning, and reduce inflammatory reactions [4,5,6]. Recently, two different studies, both in models of chronic constriction injury (CCI), have reported that HBOT effectively reduced neuropathic pain [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In hyperbaric oxygen treatment (HBOT), patients are treated with 100% oxygen under pressures higher than 1.4 absolute atmospheres (ATA), usually to promote wound healing, dilute carbon monoxide poisoning, and reduce inflammatory reactions [4,5,6]. Recently, two different studies, both in models of chronic constriction injury (CCI), have reported that HBOT effectively reduced neuropathic pain [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In light of the importance of oxygen in wound healing, scientists have been looking for different ways to supply oxygen. Hyperbaric oxygen therapy, on the other hand, is a new way of utilizing high-pressure oxygen for several specific wounds, such as radiation injuries, infections, burns, scratches and cuts, and diabetes mellitus, which cannot be healed with the conventional treatment modalities [43,44]. This method uses oxygen at a pressure higher than sea level pressure.…”
Section: Box 2 Tissue Engineeringmentioning
confidence: 99%
“…Refractory wounds pose a significant challenge for clinical intervention, resulting in great psychological stress to patients and greatly increasing their sufferings and economic burden. 3 Traditional phototherapies, such as infrared therapy and low-level laser therapy (LLLT), can effectively heal skin wounds. The biological effects of laser therapy promoted by these therapeutic methods are similar and involve a decrease in the number of inflammatory cells, increased fibroblast proliferation, stimulation of angiogenesis, formation of granulation tissue and increased collagen synthesis.…”
Section: Introductionmentioning
confidence: 99%